2010
DOI: 10.1590/s1516-35982010000900004
|View full text |Cite
|
Sign up to set email alerts
|

Production, nutritional status and chemical properties of soils with addition of cattle manure, reactive natural phosphate and biotite schist in Massai cultivar

Abstract: -The objective of this work was to evaluate the effects of cattle manure, reactive natural phosphate and biotite schist on the soil fertility, yield and nutritional status of Megathyrsus spp. cv. Massai. The experiment was conducted under field conditions, in a dystrophic Red Yellow Latosol (Oxisol). It was used a randomized block experimental design with the following treatments: three natural reactive rock phosphate from Algeria (Djebel-Onk) doses (0, 100 and 200 kg ha -1 of P 2 O 5 ), three biotite schist d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
(6 reference statements)
0
10
0
1
Order By: Relevance
“…The addition of animal waste, mainly via poultry litter in treatment NTPL, increased the Ca and CEC pH7 levels. In GrP, cattle droppings increased the P and K concentrations, which are related to urine and manure droppings (Moreira et al, 2010).…”
Section: Physical and Chemical Soil Propertiesmentioning
confidence: 93%
See 1 more Smart Citation
“…The addition of animal waste, mainly via poultry litter in treatment NTPL, increased the Ca and CEC pH7 levels. In GrP, cattle droppings increased the P and K concentrations, which are related to urine and manure droppings (Moreira et al, 2010).…”
Section: Physical and Chemical Soil Propertiesmentioning
confidence: 93%
“…On the other hand, the cattle droppings in GrP resulted in significant increases in most elements such as K, Na, due to the high concentration of these elements in bovine urine; and P, Mg and Ca, due to their concentration in cattle dung (Moreira et al, 2010). Also noteworthy was the significant increase in Fe, Al and Si concentrations in the soil solution under grazed pasture (GrP), which may be associated with processes of mineral dissolution/transformation (Azevedo et al, 1996;Officer et al, 2006;Zanelli et al, 2007;Inda et al, 2010;.…”
Section: Chemical Composition Of the Soil Solutionmentioning
confidence: 99%
“…According to Vilela et al (2002), the P and N deficiency is the most frequent cause of loss in pasture productivity and increased environmental degradation. It has often been shown that in soil with high deficiency of P, only the application of N has little impact on crop yields, as its application plus P can drastically increase the response to the fertilizer applied (Moreira and Malavolta 2001;Singh 2001;Dwivedi et al 2003;Moreira et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the promising results described by Moreira et al (2010) with the application of cattle manure, by Miranda et al (2005) with lime, and with both products by Souza et al (2010), few studies have reported the positive effects of this management practice on crop yield and soil chemical properties.…”
Section: Introductionmentioning
confidence: 99%